Dynamics and New Paradigm of Islamic Education in Indonesia - Anshori, Afif; Solikhah, Nur Amalia; Aqli, Dana Rosyidal; Musyafa’, M. Ali; Apriyanto, Sigit (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2022)
This paper aims to analyze the dynamics and new paradigm of Islamic education in Indonesia from a historical perspective. This study uses the library to research reference books, journals, archives, documents, and other writings relevant to the title under study. This research is historical research and the object is the dynamics and new paradigm of Islamic educational institutions that grew and developed in Indonesia before and after Indonesia's independence. The new paradigm of Islamic education in Indonesia is through the realization of three dimensions of the substance of Islamic education, namely the acquisition of students towards science; the realization of students towards science in the format of their attitudes or behavior towards the learning environment, and even towards society; and the synergy between the acquired knowledge and their actualized attitudes or behavior in everyday life. Then, a new paradigm of Islamic education emerged, namely the Hadhari paradigm, which is an educational paradigm that connects education in an integral-interconnective way.